Sexuality and DST/Aids in a university population - Bento , Isabel (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Basis: considering the actual si-tuation characterized b y an incre-asing sexual liberation and, there-fore, by the vulnerability and susceptibility of the sexual active population, especi-ally the young adults, we search to find out the le-vels of information/ non information or the difficul-ties they have to <leal with sexuality and the negoti-ation of safe sex. Aim: to find out among university students the most frequent sexual practices, the use of condoms as a way of prevention and their pro blems relate d to sexuali ty and STD /Aids, dis-cussing the presented risk situations and propo-sing educative actions directed to a program of in-formation and development of abilities in order to enable the change of behaviours and a conscious, secure and responsible exercise of sexuality. Me-thods: we worked with the action-research as we found it the most adequate to the development of the question, enabling us to find out the problems, followed by elaboration, execution, evaluation and intervention of educative actions directed to a tea-ching/learning process guided by the exercise of citizenship. This research had an humanist basis, with a quali-quantitative view. 57 university stu-dents of the 2nd year of the physiotherapy course were studied, revealing their inquietude regarding the theme and demonstrating interest on the deve-lopment ofthe research. Data were collected throu-gh interviews (questionnaire). Results: we found that the subjects presented problems regarding the exercise oftheir sexuality, having sex frequently but not always safe, revealing their unpreparedness to <leal with questions about sexuality, STD / Aids. Con-clusions: it is important to implement educative ac- . tions directed to the orientation, information and development of specific abilities for the exercise of a conscious, secure and responsible sexuality. We suggest that the health and education agents must be aware ofthose questions, guiding their attentión to educative and preventive actions on sexuality for adolescents and young adults.